Complications of percutaneous endoscopic gastrostomy-jejunostomy for levodopa/carbidopa infusion in advanced Parkinson's disease - Ana Olivares (Gastroenterology Insights, 2012)
Continuous infusions of levodopa directly into the duodenum-yeyunum is an effective therapy to reduce daily off time in an advanced stage of Parkinson's disease, but it is not without complications, particularly device related problems. We present our experience in three Spanish hospitals with these complications, including a severe case with migration, several decubitus ulcers, and one case of perforation of the bowel and finally death.